Narrative Discourse in Young and Older Adults: Behavioral and NIRS Analyses - Martin, Charles-Olivier; Pontbriand-Drolet, Stéphanie; Daoust, Valérie; Yamga, Eric; Amiri, Mahnoush; Hübner, Lilian C.; Ska, Bernadette (Frontiers in Aging Neuroscience, 2018)
Discourse comprehension is at the core of communication capabilities, making it an important component of elderly populations’ quality of life. The aim of this study is to evaluate changes in discourse comprehension and the underlying brain activity. Thirty-six participants read short stories and answered related probes in three conditions: micropropositions, macropropositions and situation models. Using NIRS, the variation in HbO2 and HbR concentrations was assessed throughout the task. The results revealed that the older adults performed with equivalent accuracy to the young ones at the macroproposition level of discourse comprehension, but were less accurate at the microproposition and situation model levels. Similar to what is described in the CRUNCH model, older participants tended to have greater activation in the left dorsolateral prefrontal cortex while reading in all conditions. Although it did not enable them to perform similarly to younger participants in all conditions, this over-activation could be interpreted as a compensation mechanism.